Pemanfaatan Limbah Biomassa Sebagai Plastik Biodegradable Yang Diaplikasikan Pada Food Packaging Ransum Tni - Aritonang, Sovian; Rhomadon, Fajar Ismail; Hapsari Subiakto, Amadea Kenyoning; Nismarawati, Ardine Kusuma (Fakultas Teknik UMSU, 2024)
The use of conventional plastic in the manufacture of Indonesian National Army (TNI) ration packaging has become an unavoidable standard because it provides strength, resilience and durability which is very important for protecting food and other materials. However, the use of conventional plastic in making ration packaging has become an increasingly pressing problem, especially regarding environmental sustainability. To overcome this problem, conventional plastic must be replaced with environmentally friendly plastic (biodegradable plastic). The method used is a literature review by comparing the Indonesian National Standards with literature from various journals. The results of literature research show that there is no biodegradable plastic that meets SNI 7818:2014. The mechanical properties and biodegradability of biodegradable plastics are influenced by the concentration of additives such as plasticizers and fillers, such as glycerol and chitosan.